Routine monitoring of visual outcome of cataract surgery. Part 2: Results from eight study centres. Issue 1 (21st December 2004) - Limburg, H; Foster, A; Gilbert, C; Johnson, G J; Kyndt, M; Myatt, M
Abstract : Aim: To determine whether monitoring of cataract outcome can be implemented as a routine activity in different hospital settings in Africa and Asia, and to assess the impact of routine monitoring. Methods: Eight eye centres in Asia and Africa were involved in the study between 1 June and 31 December 2000. Seven centres used a specifically designed cataract surgery record form with computerised data entry and analysis (CCSRF), and one centre used a manual recording form (MCSRF). Data were used to evaluate quality of data entry, follow up after surgery, and to assess trends in the proportion of complications and visual outcome after surgery. Findings: The reporting systems were accepted and used by all centres, and data were recorded for 5198 cataract operations. Overall, 54% of eyes were followed for 8 weeks or more and 41% for 6 months. Follow up rates varied between centres from nil to almost 100%. Visual acuity tended to improve over time. The outcome could be improved at all follow up periods by providing best spectacle correction. At 8 weeks or more follow up, surgical complications or inadequate spectacle correction accounted for 72% of the causes of poor outcome. Three centres showed a significant reduction in complication rates over the course of the 6 month study. Data entry was identified as a problem and the CCSRF software has been modified to include consistency checks to reduce data entry errors. Conclusion: A simple system to monitor cataract outcome has been successfully field tested. The results suggest that monitoring can sensitise surgeons to quality control, which can lead to a decrease in complication rates and improved visual outcomes.